Rare Case: Unilateral Acute Primary Angle-closure Glaucoma After Colonoscopy in Malang, East Java, Indonesia - Supriono Supriono; Amalia Nurul Hatinah; Mochamad Fachrureza; Syifa Mustika; Bogi Pratomo Wibowo (Interna Publishing, 2023)
Glaucoma is a heterogeneous group of optic neuropathies characterized by a progressive loss of retinal ganglion cells (RGCs) with corresponding visual field defects, and one of the main risk factors is elevated intraocular pressure (IOP). Furthermore, colonoscopy procedures require insufflation of the colon lumen with gases which can increase intraabdominal pressure (IAP) and ends with an elevation of IOP. Glaucoma is an infrequent complication due to colonoscopy; in this case, a 63 years-old woman was diagnosed with glaucoma after a colonoscopy procedure. A few hours after the colonoscopy, the patient suffered blurred vision in the left eye, and the physical examination revealed mixed conjunctival and ciliary injection with visual acuity of 1/300. There was an increase in IOP with a value of 40,2 mmHg on Schiotz tonometry. This case presented the pitfalls of the procedure and the importance of taking glaucoma awareness before a colonoscopy.